2017
DOI: 10.15376/biores.13.1.86-103
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Wood Storage on the Chemical Composition and Indigenous Microflora of Eucalyptus species Used in the Pulping Industry

Abstract: Lipophilic extractives naturally occurring in wood tend to coalesce during pulping to form pitch deposits, which have particularly undesirable effects on the pulping process and quality of pulp produced. A chemical characterization of different eucalypt species [Eucalyptus nitens, E. grandis, and E. dunnii (of different site qualities)] wood and generated pulp was performed. This study aimed at determining the effects of wood storage at -20 °C (for 6 months), by examining their chemical composition and indigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although the results found for A. mearnsii are slightly higher than that found for eucalyptus wood, it should be considered that the storage time, genetic improvement, geographical and climatic conditions have a direct influence on the extract concentration. 16,28 In a study carried out for eucalyptus, the authors showed that the storage time of 180 days can reduce up to 70% of lipophilic extracts due to biological decomposition and exposure to weathering. 13 In this context, we considered that the A. mearnsii lipophilic extracts were analyzed from the fresh material without remaining in stock.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results found for A. mearnsii are slightly higher than that found for eucalyptus wood, it should be considered that the storage time, genetic improvement, geographical and climatic conditions have a direct influence on the extract concentration. 16,28 In a study carried out for eucalyptus, the authors showed that the storage time of 180 days can reduce up to 70% of lipophilic extracts due to biological decomposition and exposure to weathering. 13 In this context, we considered that the A. mearnsii lipophilic extracts were analyzed from the fresh material without remaining in stock.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that storing the chips at − 20 °C had similar effects on the decrease of lipophilic wood extractives than seasoning does. During six months of storage, 25-44% reduction of lipophilic extractives was observed [118].…”
Section: Wood Storage and Biological Treatmentmentioning
confidence: 99%
“…Otherwise, chip deterioration and wood decay due to sap stain and a fungal attack occur [104]. Ramnath et al [118] even found variations in bacterial and fungal communities on frozen stored wood chips. They showed that storing the chips at − 20 °C had similar effects on the decrease of lipophilic wood extractives than seasoning does.…”
Section: Wood Storage and Biological Treatmentmentioning
confidence: 99%
“…During the wood storage, the extractives degraded, which resulted in changes in percentages, especially at the beginning of storage. A decrease in extractives the storage was observed by the authors Ramnath et al [32], Günther et al [33], and Giesel et al [34] as well.…”
Section: Resultsmentioning
confidence: 63%